Little Doctor Virtual Training With Snow Ball Technique In Pandemic Covid 19 Era In Elementary School In Malang - Balbeid, Merlya; Pratamawari, Dyah Nawang Palupi; Listari, Khusnul Munika; Abidin, Zefry Zainal; Subekti, Trias Arlis; Nisa, Renita Rahma Chairu (Journal of Innovation and Applied Technology, 2022)
Even in this Pandemic Covid 19, counseling is not done face-to-face, because it avoids the risk of transmission Covid-19 virus. The method was through audiovisual media with online meeting. This activity was carried out using the snow-ball technique, 6 elementary schools doing this activity. The activity started with dental training through the zoom with room separation in breakout rooms. After that were held for Little Doctors activities to educate 5 friends. Results obtained from the pre-test and post-test, the percentage of correct answers was below 50% on pre-test, while in the post-test results the percentage of correct answers was above 50% and some even 100% correct. There is a difference knowledge level oral health of students by little doctor with online education in pandemic Covid-19 Era in elementary school Malang.